The Impact of Corporate Governance on Dividend Pay-out Ratio Policy During the Covid-19 Era: The Study Case in the Basic Material Industry in Indonesia - Wendra Hartono; Kazia Laturette; Kartikasari Gunawan (AIBPM Publisher, 2023)
The purpose of this study is to analyze the impacts of Good Corporate Governance during the Covid -19 era on the dividend payout rasio policy in Indonesia. During Covid-19 era, the Basic Materials industry has faced big challenges due to lock down policy occured in many big areas which can lead to disruptive global economic supply chain. Increasing income in many Basic Material industry, can cause the percentage payment of dividends during the year of 2020 proposed by Director boards and Commissioner boards. In this research will show and compare the condition of Basic Material industry before and during Covid-19 pandemic. This reseach is categorized as quantitative research which the sample used is gathered from secondary data, financial report, from basic material industry for public listed company in the Stock Exchange of Indonesia during 2018 – 2020, with a total number of 43 companies. There are 4 independent variables are being researched, which are the Independent Commissioner, the Board of Directors, the Board of Commissioners and the Audit Committee, meanwhile the dependent variable is dividend payout ratio. The finding shows that Audit Committee (AC) is the only a significant variable that influence the Dividend Payout Ratio in the Basic Material Industry in Indonesia before COVID-19 pandemic, but it does not have a significant influence during COVID-19 pandemic.